Hubungan Paparan Screen Time, Kebiasaan Sarapan, Konsumsi Buah Dan Sayur Dengan Status Gizi Pada Mahasiswa Fakultas Ilmukesehatan Universitas Indonesia Maju Jakarta - Tria Nur Andini; Lulu’ul Badriyah; Retno Inten Rizqi (Program Studi Gizi UNSIKA, 2024)
Nutritional status can be influenced by a balanced nutritional intake. Apart from that, nutritional status is also influenced by several other factors such as exposure to screen time and breakfast habits. This study aims to determine the relationship between screen time exposure, breakfast habits, fruit and vegetable consumption on the nutritional status of FIKES UIMA students in 2023. This research uses a cross sectional method. The research was conducted in July 2023, the sample in this study consisted of 95 students. Sampling used probability sampling techniques. The bivariate analysis used was the chi-square test. The results of the chi-square test on the nutritional status variable showed that the majority of respondents had normal nutritional status, namely 75.8%, respondents who had high screen time exposure were 94.7%, had regular breakfast habits of 47.4%, and consumed fruit and vegetables. good 13.7%. The results of bivariate analysis showed that there was no relationship between screen time exposure and breakfast habits on nutritional status with p-values of p=0.821 and p=0.960, respectively. Meanwhile, fruit and vegetable consumption has a significant relationship with nutritional status (p=0.001). It can be concluded that the variable that is related to more nutritional status is fruit and vegetable consumption. Keywords: Screen time, breakfast habits, fruit and vegetable consumption, nutritional status